2017
DOI: 10.1017/ipm.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Service users’ experiences of mental health tribunals in Ireland: a qualitative analysis

Abstract: Objectives. To explore the mental health tribunal experiences of people admitted involuntarily under the Mental Health Act 2001.Methods. Employing a qualitative descriptive study design, data were collected from 23 service users who had experienced mental health tribunals during a recent involuntary admission. Face-to-face semi-structured interviews were conducted 3 months post-revocation of their involuntary admission order. Data were analysed using an inductive thematic process.Results. The majority of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…A range of barriers and facilitators to participation were identified within the literature. One study in Ireland found that having the opportunity to share ones' views and having these listened to reinforces that individuals' perspectives are valued (Murphy et al, ). Nonetheless, tribunal cultures have been condemned as a barrier to participation with the weighting afforded to psychiatric evidence and the use of reports perceived to be inaccurate being particular issues (Murphy et al, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A range of barriers and facilitators to participation were identified within the literature. One study in Ireland found that having the opportunity to share ones' views and having these listened to reinforces that individuals' perspectives are valued (Murphy et al, ). Nonetheless, tribunal cultures have been condemned as a barrier to participation with the weighting afforded to psychiatric evidence and the use of reports perceived to be inaccurate being particular issues (Murphy et al, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…One study in Ireland found that having the opportunity to share ones' views and having these listened to reinforces that individuals' perspectives are valued (Murphy et al, ). Nonetheless, tribunal cultures have been condemned as a barrier to participation with the weighting afforded to psychiatric evidence and the use of reports perceived to be inaccurate being particular issues (Murphy et al, ). In addition, inaccessible jargon, not being able to challenge evidence as it is presented, being the last person to speak during proceedings and being discouraged from speaking altogether reduces autonomy and disrupts the participatory potential of the tribunal (Livingston et al, ; Murphy et al, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 3 more Smart Citations